Analysing the impact of the 50:22 kick law changes in South African rugby tournaments between 2021 and 2022 - Strydom, W.; Vaz, L.; Tucker, R.; Kraak, W. (Science and Medicine in Football, 2024)
Tactical kicking plays a crucial role in rugby union, influencing both attacking and defensive strategies and potentially impacting a team`s overall success. The introduction of the 50:22 law requires defensive teams to reposition players to anticipate and counter kicks, thereby reducing the number of players in their defensive front line. This study investigated the impact of the 50:22 kicking law on kicking profiles by comparing the 2021 and 2022 seasons, as well as examining the success rate of 50:22 kicks during the 2022 season in South African rugby union tournaments. A retrospective research design was employed, utilising video-based performance analysis software (Nacsport Scout Plus) for data collection. The analysis encompassed all general play kicks from 177 matches spanning two seasons and tournaments, amounting to a total of 6,479 kicks. Within this dataset, there were 53 successful 50:22 kicks out of 162 attempts. Key findings revealed an upswing in kicks by scrum halves (2021: 20%, 2022: 26%; p = 0.00) and a concurrent decline in kicks by fullbacks (2021: 21%, 2022: 18%; p = 0.01). Notably, there was a significant increase in the percentage of kicks occurring in the fourth quarter of the match (2021: 20%, 2022: 22%; p = 0.01). Furthermore, the study identified a noteworthy increase in the percentage of kicks following a turnover (2021: 2%, 2022: 3%; p < 0.01). In conclusion, this research contributes valuable insights into how the 50:22 law shapes kicking strategies in South African rugby union, shedding light on the shifts in player roles and temporal patterns of kicking within the context of this specific law.